RISK-ORIENTED APPROACH IN FORMING SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY UNDER DIGITAL TRANSFORMATION - KMYTIUK, Tetiana; BILYK, Tetiana; KACHAN, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The modern economy is characterized by the active use of digital technologies as one of the key factors of economic growth. Digital transformation creates new opportunities for development, but at the same time it creates risks and threats to economic stability, competitiveness of national economies, social balance and security of information systems, which necessitates their timely identification and management. The article examines the features of a risk-oriented approach in shaping the sustainable development of the national economy in the context of digitalization. The main attention is focused on the systematization of risks arising in the process of digital transformation and the development of tools for their quantitative assessment. A classification of digital risks is proposed according to key groups, in particular economic, social, technological, cybernetic, environmental and institutional, which allows for a comprehensive coverage of the multidimensional nature of the impact of digitalization on sustainable development. The feasibility of using an integrated approach to assessing digital risks based on the calculation of the Digital Risk Index, which provides the ability to quantitatively determine the level of vulnerability of regions and sectors of the economy to the negative manifestations of digital transformation, is substantiated. The proposed index allows aggregating various indicators into a single generalized assessment, which increases the analytical value of the research results and creates a basis for their practical use. It is shown that the implementation of a risk-oriented approach creates the prerequisites for the formation of an adaptive system for managing the sustainable development of the national economy and minimizing the negative consequences of digital transformation.